Preparative HPLC separation of underivatized amino acids for isotopic analysis. - Tripp, J; McCullagh, J (2012)
Single-compound analysis of stable or radio-isotopes has found application in a number of fields ranging from archaeology to forensics. Often, the most difficult part of these analyses is the development of a method for isolating the compounds of interest.Here, we describe three complementary preparative HPLC procedures suitable for separating and isolating single amino acids from bone collagen or hair keratin with minimal isotopic contamination. Using preparative reversed-phase, ion-pair, or mixed-mode chromatography of underivatized amino acids in aqueous mobile phases, single amino acids can be isolated and further analyzed using mass spectrometric techniques.